Sistem Pakar dengan Proses Forward Chaining pada Kulit Wajah Berminyak - Indah Syahputri; Agus Perdana Windarto; Dedi Suhendro; Eka Irawan; M Fauzan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The research objective was to analyze oily facial skin using the forward chaining method and to build an expert system application that was able to provide accurate information about oily facial skin. Sources of data obtained by interviewing the owner of the House of Beauty who resides on Jl. Adam Malik, Pematangsiantar. The implementation of the expert system is a web application. The results showed that the system could be applied and analyzed oily facial skin using the forward chaining method, which was caused by various kinds of symptoms that attack everyone's facial skin, especially oily facial skin disease, based on the symptoms displayed by the user so that the expert system application could provide information about definition, treatment, and prevention, so as to help users in symptomatic symptoms and types of disease based on the symptoms that appear by the user.